INSTILL RELIGIOUS AND MORAL VALUES IN CHILDREN WITH SPECIAL NEEDS IN EDUCATION UNIT EARLY CHILDHOOD - Falera, Ana (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Children with Special Needs have the same right to get proper education as other normal children. This has been regulated by the government in statutory regulations. So it is important for educators and parents to provide support to children in getting an education. Every child has developmental tasks at every age that must be stimulated in order to develop optimally. One of the development tasks that must be achieved is on the aspect of religious and moral values. Children who experience visual impairment or also called blind, often experience problems in learning. Blind children need special stimulation so that their developmental tasks can be achieved. Educators need to carry out strategies that can be used to help blind children in learning. There are many stimulations that educators can do to instill religious and moral values ​​in blind children. However, after reviewing based on literature studies conducted by the author, the most effective way to instill religious and moral values ​​in blind children is through singing and habituation activities to carry out religious and moral values ​​in daily activities.